Graphene Quantum Dot Crystal Serving as a Multi‐Qubit Circuit Operating at High Temperatures. Issue 12 (20th October 2020) - Shafraniuk, Serhii E.
Abstract: Localized states (LS) of electrons are studied in clusters and in periodic arrays of graphene quantum dots (GQD) formed using narrow graphene stripes with either armchair or zigzag shape of atomic edges. Basic electronic parameters of the system such as the LS energies E n, inter‐level splitting Δ n, wavefunction coherence, and the inter‐dot coupling are controlled by applying the electric potentials φ lg to the electrodes. The electron density of states N ( ε ) of the periodic quantum dot array regarded as 1D crystal (GC) represents a sequence of very sharp peaks corresponding to LS levels. The spatial coherence parameter Ξ GC = 1 / ( d · ℑ κ ) ( d is the GC period and κ is the electron wave vector) is estimated as Ξ GC ≃ 5 to 20, suggesting that the electron coherence involves large clusters of GQD by spreading over 5–20 periods in the artificial crystal. Furthermore, the coherence time τc, which is determined by inelastic electron–phonon collisions is remarkably long, τ c ≈ 2 to 100 ns even at temperatures T ≈ 300 K. The above properties of GC open new opportunities for building of the all‐electrically controllable multi‐qubit circuits operating at high temperatures. Abstract : Electron quantization is studied in clusters and in periodic arrays of graphene quantum dots (GQD). It is found that electron density of states of the infinite periodic GQD array represents a sequence of localized levels. At temperature T ≈ 300 K, the spatial coherence of electrons spreads over 5–20 periods while the coherence time achieves 2–200 ns.